Avaliação na educação infantil: sentidos atribuídos por professores na creche - GAVA, Fabiana Goveia (2019)
This study aims to acknowledge the assigned directions by the teachers who work in daycare centers about early childhood educational assessment from the historical political context of the implementation of the “Guidelines for pedagogical studies in early childhood education in Sorocaba municipal network” (SOROCABA, 2016b). As targeted directions were: to get to know the challenges asserted by the teachers about the evaluation in the kindergarten by the guidelines of the Secretariat of Education; identify it by interviewing teachers what are their methodology on monitoring and develop children’s learning tools and their relationship to assessment and the educators' perceptions of such tools , and investigate how educators understand continuing education in the strategy implementation process. For this, an adopted research used theoretical-methodological references or historical-dialectical materialist and the perspective of historical-cultural theory, specifically, on the concept adopted in Vigotski (2008) and had the participation of four teachers from a public daycare center. Having as methodological strategies: participant observation with records in field diary, semi-structured interviews and documentary consultation. As results pointed out were that: a) an assessment in early childhood education is aimed at monitoring the child's learning and development focusing on behavioral and attitudinal issues and also allows teachers to (re) think their pedagogical practices, as well as revealed that the planning is based on teaching experiences and centered on the expectations of adults on children; b) the existence of various difficulties at school, such as precarious working conditions, high number of children in the classroom, performance of professionals with different backgrounds, teacher insecurity in reporting the children’s difficulties in the report, among other aspects; and c) the discontinuity of continuing education provision and the lack of a training policy that meets the educators’ needs. It is argued that continuing education is guaranteed and built collectively with teachers who work with children, seeking the (re) construction of evaluative practices that respect children as historical characters and their rights; It is also suggested that institutional evaluation be strengthened through greater participation by the families and the school community in order to foster democratic participatory processes on how improving the quality of public schools.